2021
DOI: 10.1186/s41927-021-00216-0
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between educational attainment and the risk of rheumatoid arthritis: a Mendelian randomization study

Abstract: Background Educational attainment is moderately heritable and inversely associated with the risk of rheumatoid arthritis. However, the causality from educational attainment on rheumatoid arthritis remained unknown. Here, we aimed to determine whether educational attainment is causally associated with rheumatoid arthritis (RA) by using Mendelian randomization (MR) approach. Methods Summary statistics data for RA were obtained from an available, publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Human health has been linked to socioeconomic status (SES) and certain individual behaviors (IB) [ 6 8 ]. Determining the effect of SES/IB on human diseases might help us formulate targeted feasible strategies to mitigate disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Human health has been linked to socioeconomic status (SES) and certain individual behaviors (IB) [ 6 8 ]. Determining the effect of SES/IB on human diseases might help us formulate targeted feasible strategies to mitigate disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Recent MR studies showed a lack of genetic causality between IBD and atrial fibrillation (42), which was consistent with our results. Although pleiotropy may cause the bias of the results in MR analysis, there is little possibility in our study (43). Because our MR analysis had more than 80% power to detect the effect of CVDs development (Supplementary material 5).…”
Section: Discussionmentioning
confidence: 98%
“…Education attainment represents an important health and social determinant associated positively or negatively with a large panel of mental and somatic diseases ( 19 ). Regarding RA, a preventive effect is repeatedly associated with a higher educational level, and such an effect is conserved following adjustment with tobacco smoking, body mass index, and intelligence ( 20 , 21 ). Indeed, in patients with RA, a higher educational level was associated with a better status including at the baseline a lower number of painful joints, less inflammation, RF seronegativity, and a higher rate of survival for men ( 22 – 24 ).…”
Section: Discussionmentioning
confidence: 99%